2006
DOI: 10.1016/j.dsr.2006.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid lateral particle transport in the Argentine Basin: Molecular 14C and 230Thxs evidence

Abstract: Recent studies have revealed that lateral transport and focusing of particles strongly influences the depositional patterns of organic matter in marine sediments. Transport can occur in the water column prior to initial deposition or following sediment re-suspension. In both cases, fine-grained particles and organic-rich aggregates are more susceptible to lateral transport than coarse-grained particles (e.g. foraminiferal tests) because of the slower sinking velocities of the former. This may lead to spatial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 70 publications
(108 reference statements)
5
30
0
1
Order By: Relevance
“…While some of the scatter in the data (Fig. 5c) could originate from the measurement uncertainties affecting both methods, we speculate that it is mostly stemming from hydrodynamic effects that lead to focusing of particles of contrasting densities (Mollenhauer et al 2006). As dinoflagellate cells and dinocysts are both composed only of organic materials of very similar densities, little differential sorting of sterols and dinocysts through lateral transport is probably occurring in the water column (both likely have very similar sinking rates).…”
Section: Comparison Of S Dinosterols and Dinocysts Distributionsmentioning
confidence: 96%
See 2 more Smart Citations
“…While some of the scatter in the data (Fig. 5c) could originate from the measurement uncertainties affecting both methods, we speculate that it is mostly stemming from hydrodynamic effects that lead to focusing of particles of contrasting densities (Mollenhauer et al 2006). As dinoflagellate cells and dinocysts are both composed only of organic materials of very similar densities, little differential sorting of sterols and dinocysts through lateral transport is probably occurring in the water column (both likely have very similar sinking rates).…”
Section: Comparison Of S Dinosterols and Dinocysts Distributionsmentioning
confidence: 96%
“…Dinocysts on the other hand likely remain free particles of lower density, and their high molecular weight, highly crosslinked, aliphatic matrix makes them highly resistant to degradation, particularly in anoxic environment (Kokinos et al 1998;Gélinas et al 2001;Arzayus and Canuel 2004). Resuspension of sediments can therefore influence depositional patterns and lead to the spatial and, possibly, temporal decoupling of dinocysts and 4a,23,24-sterols (Mollenhauer et al 2006), particularly in high-energy environments such as ocean margins and slopes, or in the vicinity of river mouths. Only the coupled compoundspecific radiocarbon analysis of 4a,23,24-sterols and dinocysts from individual samples would allow testing this hypothesis.…”
Section: Comparison Of S Dinosterols and Dinocysts Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(For the latter, see e.g. Mollenhauer et al 2006). The influx of anthropogenic carbon, mostly from fossil fuel burning and spills have been extensively investigated (Reddy et al 2002a,b;Tanner et al 2004;Slater et al 2005Slater et al , 2006Smittenberg et al 2005;White et al 2005;Wakeham et al 2006).…”
Section: Biogeochemistry and Microscale Amsmentioning
confidence: 99%
“…Mollenhauer et al (2006) showed combined 14 C and 230 Th xs data for the Argentine Basin. In this region, independent evidence exists for lateral displacement of alkenone-bearing particles (Benthien and Müller, 2000;Rühlemann and Butzin, 2006).…”
Section: Introductionmentioning
confidence: 99%